A catalytic and tert-butoxide ion-mediated amidation of aldehydes with para-nitro azides - Carbone, Giorgio; Burnley, James; Moses, John E. (Royal Society of Chemistry, 2013)
We report here a new catalytic reaction in which, p-nitro azides are acylated by aldehydes to produce amides and molecular nitrogen in a single step. The transformation is believed to proceed via an electron transfer process mediated by the tert-butoxide ion, and catalysed by a thiazolium salt derived species.